2014
DOI: 10.1186/1476-511x-13-115
|View full text |Cite
|
Sign up to set email alerts
|

Metformin enhances nitric oxide production and diminishes Rho kinase activity in rats with hyperlipidemia

Abstract: BackgroundRho kinase over-activation is associated with nitric oxide (NO) reduction and atherosclerosis. Metformin is favorable for endothelial function improvement and cardiovascular outcomes. Whether cardio-protective effect of metformin is associated with Rho kinase activity is unknown.MethodsHyperlipidemia model of rats were established accordingly. Thereafter, medical interventions in terms of atorvastatin, metformin or combined therapy were administered for 4 weeks. Laboratory parameters were compared am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…And results from previous researches also indicated that the cholesterol-independent benefits derived from statins therapy were at least partially dependent on ROCK inhibition [20,24,25]. Notably, consistent with experimental findings [15,26,27], data from our present clinical research also supported the concept that metformin has additional vascular-protective effects other than glucose-modulation. Compared to the control group, the variables including the rate of obese, Hs-CRP level, ROCK2 and NO concentrations were improved more profoundly in the combined group (p < 0.05).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…And results from previous researches also indicated that the cholesterol-independent benefits derived from statins therapy were at least partially dependent on ROCK inhibition [20,24,25]. Notably, consistent with experimental findings [15,26,27], data from our present clinical research also supported the concept that metformin has additional vascular-protective effects other than glucose-modulation. Compared to the control group, the variables including the rate of obese, Hs-CRP level, ROCK2 and NO concentrations were improved more profoundly in the combined group (p < 0.05).…”
supporting
confidence: 90%
“…And through inhibiting RhoA/ROCK signaling pathway, statins confer pleiotropic effects including endothelium-protection and anti-inflammation on cardiovascular system [13,14]. Interestingly and importantly, our recent findings indicated that through diminishing ROCK concentration, metformin administration enhanced NO production in rats with dyslipidemia [15]. Therefore, we hypothesized that statins plus metformin might provide additive benefits on NO production through their synergistic effects on reducing ROCK concentration.…”
Section: Discussionmentioning
confidence: 93%
“…Metformin improves vascular function via attenuation of IR/hyperinsulinemia [19], and can also decrease serum levels of asymmetric dimethylarginine (ADMA), an endogenous inhibitor of NO synthase, by modulating androgen levels and insulin action [34]. In addition, metformin stimulates AMPK and phosphorylates endothelial nitric oxide synthase (eNOS) [19,35], while it enhances NO levels and diminishes Rho kinase in animal models of hyperlipidemia [36]. However, in the present study we have no detected differences in NO levels between control and PCOS subjects either in basal conditions or after metformin treatment.…”
Section: Discussionmentioning
confidence: 98%
“…There is evidence, that metformin treatment activates AMPK signaling pathway and promotes phosphorylation of endothelial NO synthase (Liu et al ., ). Metformin increases α‐subunit activity of AMPK by its phosphorylation, as well as increase the expression of eNOS and thus increase the bioavailability of NO (Davis et al ., ).…”
Section: Introductionmentioning
confidence: 97%